STUDENT ABSENCE INFORMATION SYSTEM AT PANCUR IDO ELEMENTARY SCHOOL USING RAPID APPLICATION DEVELOPMENT METHOD - Michael Hordianta Bangun (Bahasa Indonesia, 2022)
At Pancur Ido Elementary School, student attendance is written in the attendance book that has been provided by the school management. Student attendance will be filled in by the subject teacher who will then report once a month to the school principal. This system is of course very inefficient and ineffective in monitoring student attendance. Parents of students will also find it difficult to monitor their child's attendance. Based on the results of the analysis, design, and testing of student attendance information system applications as discussed in previous chapters, the authors can conclude: Student Absence Information System is an integrated system that is very important in processing, analyzing, and evaluating as well as supporting decision making to monitor student attendance due to absence data quickly, precisely and efficiently